Intellectual Property Regimes to Protect Computer Software: Indonesia and the United States - Denindah Olivia (LEGAL BRIEF, 2020)
The national’s legal framework consists of separated regimes on protecting Intellectual Property Rights. One of them being possibly one of the oldest regimes that is copyright, is a declarative protection which makes it distinctive than other regimes. Considering that copyright is an Intellectual Property right that is easier to obtain with respect of the nature of the protection itself, therefore making copyright a popular method in protecting software, including in Indonesia. However, a more developed nation such as The United States covers the protection of software through copyright and patent protection. This paper will analyze Copyright regime in Indonesia for protecting computer software through a practical comparison to the United States. The aim of this paper is to furthermore examine on how copyright regime is the most suitable protection for computer software in Indonesia. Keywords: Computer Software, Copyright, Intellectual Property Rights, Indonesia, The United States.